Fracture resistance after root canal filling removal using ProTaper Next, ProTaper Universal Retreatment or hybrid instrumentation: an ex vivo study - Hadeel Hassan Hanafy; Marwa Mahmoud Bedier; Suzan Abdul Wanees Amin (Restorative Dentistry & Endodontics)
ObjectivesThis study evaluated the effect of ProTaper Next (PTN), ProTaper Universal Retreatment (PTR) and hybrid instrumentation (HI) for canal filling removal on the fracture resistance (FR), mode of failure (MoF), and filling removal time.Materials and MethodsNinety-six, mandibular premolars were decoronated and randomly divided into 6 groups (n = 16), as follows: sound (S), untreated canals; prepared teeth (P), canals only prepared to ProTaper Universal finishing instrument (F4); endodontically-treated (ET), prepared and obturated canals using the single-cone technique; and groups PTN, PTR, and HI where filling was removed using PTN, PTR, or HI respectively. FR under vertical loading; MoF and time were assessed. Data were analyzed (Significance level [α] = 0.05).ResultsThere was a significant difference in FR among all groups (p < 0.001) (HI < P < PTN < S < ET < PTR). HI showed lower FR than S, ET and PTR, and P showed lower FR than PTR (p < 0.05). For experimental groups, there was a significant difference between every group pair (p < 0.05) No significant difference was found regarding MoF distribution (p > 0.05). HI required the highest filling removal time, while PTR required the least (p < 0.05 between every group pair).ConclusionsThe effect of filling removal on FR may depend on the filling removal technique/system used. PTR could be faster and protect against fracture followed by PTN; HI could adversely affect FR. FR may be associated with filling removal time.